Research update on cell membrane camouflaged nanoparticles for cancer therapy - Wang, Chengfang; Wu, Size (Frontiers in Bioengineering and Biotechnology, 2022)
Cell membrane-camouflaged biomimetic functionalization of nanoparticles has emerged as a promising strategy for cancer theranostics. These cell membranes used for camouflaging are generally isolated from natural or engineered erythrocytes, neutrophils, macrophages, T lymphatic cells, stem cells, and cancer cells. The camouflaging strategy of coating nanoparticles with cell membranes allows for tumor homotypic targeting through self-recognition as source cells, immune evasion, and a prolonged blood circulation time, thereby improving the effective payload delivery and tumor therapy. More so, some engineered cell membranes with functionalized peptides, proteins and moieties on membrane surface can be transferred for therapy in the same time. In this review, we summarized the latest research on various types of cell membrane-camouflaged nanoparticles aimed at anti-cancer therapy, focusing on the biological advantages of different cell membranes, constitutions of nanoparticles, fabrication processes, key findings, potential therapies, and discussed the major challenges and future opportunities.